The Influence of Psychological and Physiological Individual Features on the Formation of His Lingual Qualities - Lavrynenko, Oleksandr (East European Journal of Psycholinguistics, 2015)
In this article the empirical research of the role of the distinguished physiological-psychological factors in the process of lingual qualities formation on the level of lingual ability, lingual capacities and lingual competence is described. This research of human personality’s lingual qualities has been carried out to three vectors: the search of positive and negative correlations between the basic human character features and the set of lingual qualities; the conduction of the differential analysis of human lingual qualities between the male and female respondents-groups with the aim to define the most meaningful differences; the experimental search of the most optimal functional interrelation between logical and image thinking inside of personality, which is going to be most preferable for fast lingual qualities development. In the process of the described research it was finally defined, that every of the above mentioned factors has it’s own very specific influence on the formation and development of human lingual qualities. References Аnanyev, B. (1980). Izbrannyye Psihologicheskiye Trudy [Selected Psychological Works]. Moscow: Pedagogika. Kostyuk, G. (1989). Navchalno-Vyhovnyi Protses i Psyhichnyi Rosvytok Osobystosti [The Teaching Process and Psychical Development of Personality]. Kyiv: Radyanska Shkola. Krasnykh, V. (2001). Osnovy Psiholingvistiki i Teorii Kommunikatsii [Fundamentals of Psycholinguistics and Theory of Communication]. Moscow: Gnosis. Krylov, А. (2000). Praktikum po Obshchey, Eksperimentalnoy i Prikladnoi Psihologii [Practical Guide to General, Experimental and Applied Psychology]. S.-Petersburg: Piter. Lavrinenko О. (2013). Genderni Osoblyvosti Movnyh Yakostei Studentiv v Protsesi Vykladannya Inozemnoyi Movy [Gender Peculiarities of Students’ Lingual Qualities in the Process of Foreign Language Teaching]. Rivne: Rivne State Humanitarian University. Leontyev, A. (2004). Deyatelnost, Soznaniye, Lichnost [Activity, Consciousness, Personality]. Moscow: Pegagogika. Leontyev, A. (1983). Izbrannye Psihologicheskiye Proizvedenija [Selected Psychological Works]. Moscow: Pegagogika. Luria, А. (2006). Osnovy Neiropsihologii [Fundamentals of Neuropsychology]. Moscow: Moscow University. Luria, А. (1979). Yazyk i Soznaniye [Language and Consciousness]. Moscow: Nauka. Trofimov, J., Alekseyeva, М. (2001). Psyhologiya [Psychology]. Kyiv: Lybid. Ushakova T. (2006). Psiholingvistika: Sbornik Metodik Issledovaniya Lichnosti [Psycholinguistics: Collection of Methods for Personality Research]. Moscow: Perse. Ufimtseva N. (1988). Biologicheskiye i Sotsyalnye Factory v Rechevom Razvitiyi [Biological and Social Factors in the Speech Development]. Moscow: Nauka. Vishnevsky О. (1992). Dovidnyk Vchytelia Inozemnoyi Movy [The workbook for teacher of foreign language]. Kyiv: Radyanska Shkola. Zalevskaya, А. (2000). Vvedenije v Psiholingvistiku [Introduction to Psycholiguistics]. Moscow: Russian State University for the Humanities.